GAMBARAN EVALUASI TEKANAN DARAH PADA KONSUMEN PRODUK OLAHAN DAUN Spondias Pinnata (L.f) Kurz - Anastasia, Ni Putu Sintya; Wismayanti, Kadek Wiwin Dwi; Raya, Nyoman Agus Jagat; Ita Wulandari, Ni Putu (Coping: Community of Publishing in Nursing, 2024)
Hypertension is a medical condition where the systolic blood pressure is above 140 mmHg and the diastolic blood pressure is above 90 mmHg. The number of people suffering from high blood pressure can affect public health. One way to lower blood pressure is by using processed Spondias pinnata (L.f) Kurz (cemcem) leaf products. The aim of this research is to determine the effects of consuming processed Spondias pinnata (L.f) Kurz leaf products on blood pressure levels. This research uses a quantitative descriptive approach with a non-analytical cross-sectional design. The study was conducted on consumers of processed Spondias pinnata (L.f) Kurz leaf products in Bali. The sample size was 30 individuals aged 18 to 80 years old. The sampling technique used was purposive sampling, with the criteria of consuming processed Spondias pinnata (L.f) Kurz leaf products within one month and not taking antihypertensive drugs. The results show that consuming processed Spondias Pinnata (L.f) Kurz leaf products can help lower blood pressure in consumers. These products provide benefits for consumers in maintaining their blood pressure in the normal range. This research can be used as a basis for developing intervention trials to reduce cases of hypertension in the community.